Overview of finger friction and tactile perception. Issue 4 (5th December 2018) - Zhou, Xue; Mo, Ji Liang; Jin, Zhong Min
Abstract : A tribological phenomenon usually occurs when fingers move against object surfaces. Friction plays an essential role during this process as well as in the corresponding tactile perception. This work focuses on an overview of finger friction and tactile perception, particularly from a synergistic perspective. A wealth of literature was analysed to summarise the current trend in research methods and contents in this area. The corresponding gaps in earlier studies and a trend analysis are provided in this study.